IMPLEMENTASI KEBIJAKAN INTERDEPENSI FAKTA-NILAI DALAM PROSES PENGINPUTAN DATA POKOK PENDIDIKAN (DAPODIK) DI SEKOLAH SATUAN PENDIDIKAN KERJASAMA GREEN SCHOOL BALI - Ni Putu Tirka Widanti (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
Indonesia's national education planning program includes an integrated data collection called DAPODIK, or Basic Education Data, which serves as the main data source for the country's education system. Educational planning will fail if it is not carried out by professionals. In this dapodik system, all data required for the application is complete, original (legal), responsible, and up-to-date. improve education in Indonesia and save unnecessary expenses so that these savings can be used to support education programs that are more in line with the needs of the Indonesian people, using data from this dapodik application, the central government will be able to make decisions about staff ratios in education, professional allowances educators, and school operational costs.